Оцінка безпеки експлуатації гідротехнічних споруд на малих річках під час проходження дощових (зливових) паводків - Гапіч, Геннадій Васильович; Hapich, Hennadiy (My University, 2016)
Встановлені дамби, що мають потенційну небезпеку руйнування внаслідок переливу води через гребінь гідротехнічних споруд. Розрахований додатковий об’єм води, який здатні акумулювати водойми. На основі гідрологічних розрахунків у басейні р. Нижня Терса, визначені максимальні витрати та об’єми води під час проходження дощових (зливових) паводків. The results of hydrological calculations in the basin on the river Lower Tersа. Determine the maximum flow rate and volume of water rain storm floods. The technical condition of groundwater dams on reservoirs is researched. Survey shows poor condition of spillway facilities. It means the danger of the destruction dams by entering the body of water large quantities of water. Built map and definition of the catchment area of the river Lower Tersа. On the basis of hydrological calculations established structures that sustain breakthrough dams upstream.
Safety assessment of exploitation hydraulic structures on the small river during rain floods
Keywords: гідротехнічна споруда; hydraulic structure; дамба; dam; водосховище; reservoir; річка; river